Communication and democratic reform in South Africa - Horwitz, Robert Britt (Cambridge University Press, 2001)
The book examines the reform of the communication sector in South Africa in the transition from apartheid to democracy. It studies the complex political process by which broadcasting, telecommunications, the state information agency, and the print press were transformed from apartheid-aligned apparatuses to accountable democratic institutions.
Keywords: Communication policy -- South Africa.; Democracy -- South Africa.; Communication -- Politique gouvernementale -- Afrique du Sud.; LANGUAGE ARTS & DISCIPLINES -- Communication Studies.; Communication policy; Democracy; South Africa; Demokratisierung; Kommunikation; Massamedia.; Overheidsbeleid.; Democratie.; Démocratie -- Afrique du Sud.; Politique de la communication -- Afrique du Sud.; Médias -- Afrique du Sud.; Südafrika <Staat>; Communication.; Télécommunications.; Radiodiffusion.; Apartheid.; Démocratie.; Presse.; Réformes.; Afrique du Sud.; Samfundsvidenskab -- Sociologi.; Electronic book.